Lecturas de “Hum Dekhenge” de Faiẓ Aḥmed Faiẓ. ¿Imágenes islámicas, revolución o sentimientos antihindúes? - Castro Meagher, Genoveva (El Colegio de México, 2021)
This article examines the controversy caused by the Faiẓ Aḥmed Faiẓ’s poem “Hum Dekhenge” during the protests triggered by the approval of the Citizenship Amendment Act and the National Registry of Citizens at the end of 2019 in India. In addition to a Spanish translation of the actual text, it also offers a background of the debate, a biographical sketch of the poem’s author, and diverse interpretations. The production of meaning is a complex articulation between text, readers, and the sociopolitical context. “Hum Dekhenge” is a poem of various linguistic, literary, and political registers. Without question its reading is open to multiple possibilities.